DIPLOMASI OLAHRAGA MELALUI WUSHU DALAM HUBUNGAN INDONESIA TIONGKOK TAHUN 2018 – 2023 - ', Franky; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This study explains the role of sports diplomacy through Wushu in the relationship between Indonesia and Tiongkok during the period 2018–2023. Tiongkok has long been known as a leading country in sports, especially in Wushu, which is widely recognized as a traditional Chinese martial art. The focus of the study is on Indonesia's cooperation with Tiongkok, which has made Wushu one of the instruments to strengthen diplomatic relations between the two countries. Using the theory of Sports Diplomacy, this study aims to analyze how Wushu contributes as an effective diplomatic tool in strengthening bilateral relations between Indonesia and Tiongkok. Through interviews and literature review, this study identifies the positive impact of cultural and sports exchange activities and their effect on the political and economic relations between the two countries. The findings show that sports diplomacy can play a significant role in building bridges of friendship between Indonesia and Tiongkok, with a subsequent impact on their political and economic relationships. The results of this research affirm that Indonesia, through sports diplomacy as outlined by Barry Sanders, has made Wushu an effective means to build friendship bridges between Indonesia and China. The research findings are expected to inspire other countries interested in leveraging sports as a positive diplomatic instrument to support better international relations. Keywords: Sports diplomacy, Wushu, Bilateral relations, Soft Power